Adaptive security approach for wireless sensor network using RSA algorithm - Maha Salah Asaad; Muayad Sadik Croock (Institute of Advanced Engineering and Science, 2021)
A type of distributed and self-regulating network is the wireless sensor network (WSN). The sensor nodes have limited computing capabilities, memory, battery power are needed to ensure a strong security design. In this paper, an adaptive cryptographic scheme for WSN that is operating on routing ad hoc on-demand vector routing (AODV) protocol. The adaptive term refers to the adopted mechanism between heavy and light asymmetric cryptography techniques of RSA. The heavy technique adopts the complete version of RSA algorithm, while the light one considers a reduced complexity version. This is to control the security operation over the included nodes even with low power ratio. In various case studies, the proposed scheme is checked and the result obtained shows the high efficiency of results in terms of protection guarantee.